PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PASAR PERUSAHAAN SEKTOR PERBANKAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING DI BURSA EFEK INDONESIA - Leonardus Noventa Hastimelika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aimed to test the influence of intellectual capital against the market value of the company’s banking sector through the company's financial performance. The sample used in this study amounted to 105 corporate banking sector listed in the Indonesia stock exchange. Methods for analyzing the data in this study using Structural Equation Modeling (SEM) based Partial Least Square (PLS). The results of this research indicate intellectual capital negatively affect the market value of the company. This is due to the management of intellectual capital had not been appreciated more by investors because the company's intellectual capital expenditure is seen by investors as a burden that will affect the company's profits. Intellectual capital positively affects the company's financial performance, it is because the management of intellectual capital has been used as efficiently as human capital, customer capital and structural capital can increase the company's financial performance. The results in this study stated that the financial performance successfully mediated in part (part mediating) the influence of intellectual capital with a market value of banking sector companies. The utilization of intellectual capital components can efficiently improve the company's financial performance so that with the increase of the company'sfinancial performance will be responded investor impact on increasing the company's market value.Keywords: Intellectual capital, the market value of banking, financial performance.